(untitled) (Journal of Medicine, 2008)
This descriptive study in the Infectious Disease Hospital, Dhaka, on rabies was carried out to see the patterns of presentation, age group at risk, state of vaccination following animal exposure and the interval between animal exposure and the development of the disease. Of 684 cases of rabies from June 1999 to November 2003, majority (64.18%) of the victims were within 15 years of age. Male gender (76.75%) and rural people (86.40%) constituted the bulk of the cases. 80.26% of cases had WHO category III exposure. Most of the cases were not vaccinated (86.04%). Among 93 cases who received vaccine, only 9.67% took tissue culture vaccine and 90.3% were treated with nerve tissue vaccine. None of the 684 cases were treated with RIG. Dog was the principal animal responsible for 95.76% cases. 65.93% of the cases developed the disease between 31 to 100 days after the animal exposure. DOI = 10.3329/jom.v8i1.1370 J MEDICINE 2007; 8 : 3-6 Â Â